FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN TERHADAP PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Zahirah , Afifah Nabilah; Santioso, Linda (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
The purpose of this study is to obtain empirical evidence regarding the effect of operating cash flow, profitability, leverage, and sales growth on the value of manufacturing companies listed on the Indonesia Stock Exchange in 2018 - 2020. The criteria that have been set are using a sample of 61 manufacturing companies. which have been selected using purposive sampling technique. The data is processed using Eviews version 12. Based on the results of this study, it shows that operating cash flow has a negative and insignificant effect on firm value, profitability has a positive and significant effect on firm value, leverage has a negative and insignificant effect on firm value, and sales growth has a positive effect. and not significant to firm value.